Black inventors : crafting over 200 years of success - Holmes, Keith C. (Global Black Inventor Research Projects, Inc. New YorkUS, 2008)
Covers black innovators and inventors from a global perspective. Identifies black inventors from Africa, Australia, Canada, Caribbean, Central and South America, Europe, Russia, United Kingdom and tthe United States.